The Effect of Talent Management and Innovation Digital Capability on Employee Performance - Ahmad Zaelani Adnan; Eeng Ahman; Disman Disman; Tjutju Yuniarsih; Ramayani Yusuf (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The readiness of HR in welcoming industry 4.0 is a very important thing to pay attention to. Pertamina itself is now trying hard to support vendors who have technology, inventories or industries to synergize with educational institutions to assist the government in preparing human resources that are able to compete in welcoming industry 4.0. The purpose of this study is to examine the effect of talent management and digital innovation capabilities on employee performance. The sample of this research is 150 employees of PT Pertamina RU-VI Balongan. This research design uses quantitative research with data analysis using a structural equation model (Structural Equation Modeling). Based on the results of the analysis, the structural equations model equations are Y = 0.44X1 + 0.60X2, these coefficients indicate that there is an influence of talent management and digital innovation capabilities on employee performance with a determinant coefficient (R2whichmeans 55% of management variables. talent and digital innovation capabilities can explain the performance of employees at PT Pertamina RU-VI Balongan. While the remaining 35% is influenced by other variables outside of this research variable.